EDUCATIONAL PORTAL SEEN AS A KEY COMPONENT OF INFORMATISATION OF CONTEMPORARY TERTIARY EDUCATION - Bobrytska, Valentyna (The Modern Higher Education Review, 2018)
The article reveals the role of an education portal as a key component of informatisation of modern tertiary education; proves the applicability of using of Web-pages of the educational portal in occupational activity of teachers/lecturers in the settings of informatisation of tertiary school; specifies the structural components of the educational Portal along with the main features of an educational portal of higher educational institution; gives the insights into the types of portals (horizontal, vertical) viewed as a key component of informatisation of tertiary school; highlights best practices of the use Web-portal pages in the process of professional training of students of higher educational institutions; reveals the advantages of the educational portal regarded to be the key component of informatisation of tertiary education; outlines the essential features of the basic concepts for this study.